Peningkatan Pemahaman Teori Dasar Musik pada Guru SMP di Kabupaten Bireun - Yuli Astuti; Yeni Zuryaningsih (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This research aims to describe increasing teacher understanding of music theory material. As an arts and culture teacher, you don't just focus on one area of ​​art, but you have to master all the material, including music, fine arts, theater and dance. One of the basic materials that teachers must master is basic music theory. There are still many teachers who do not understand the basic theory of music, even though this theory is the initial provision in learning music such as vocals. The method used is descriptive qualitative with pretest and posttest questionnaire data collection techniques, observation and interviews. The research was conducted for one week, the results showed an increase in understanding of basic music theory material by 97.8%. This can also be proven by the results of singing the score for the song Tanoh Lon Sayang according to the actual punctuation